Evaluation of Tp-e interval and Tp-e/QT ratio in patients with rheumatoid arthritis - Gurkan Acar; Murat Akkoyun; Alper Buğra Nacar; İmran Dirnak; Gözde Yıldırım Çetin; Makbule Nur Yıldırım; Cemil Zencir; Kayıhan Karaman; Mustafa Çetin; Mehmet Sayarlıoğlu (Türk Kardiyoloji Derneği Arşivi, 2014)
Objective: Several studies have suggested that the interval from the peak to the end of the electrocardiographic T wave (Tp-e) may correspond to the transmural dispersion of repolarization and that inreased Tp-e interval and Tp-e/QT ratio are associated with malignant ventricular arrhythmias. The aim of this study was to evaluate ventricular repolarization by using Tp-e interval and Tp-e/QT ratio in patients with rheumatoid arthritis (RA), and to assess the relation with inflammation. Study design: Ninety-six patients with RA and and 50 controls were included. From the 12-lead electrocardiogram Tp-e interval and Tp-e/QT ratio were measured. Blood samples were taken for erythrocyte sedimentation rate (ESR) and plasma levels of C-reactive protein (CRP). These parameters were compared between groups. The relationship between ventricular repolarization and inflammation was assessed by Pearson correlation coefficients. Results: Tp-e interval and Tp-e/QT ratio were increased in RA patients compared to the controls (72.6+-8.2 vs 66.4+-8.5 milliseconds, 0.20 +- 0.02 vs 0.18 +- 0.02; P<0.001 and P<0.001, respectively). Tp-e interval was significantly correlated with CRP, ESR, and disease acticity score (DAS-28) (r=0.56, P<0.001, r=0.57, P<0.001, and r=0.29, P=0.02, respectively). Tp-e/QT ratio was also correlated with CRP, ESR, and DAS-28 score (r=0.43, P<0.001, r=0.53, P<0.001, and r=0.25, P=0.03, respectively). Conclusions: Increased frequency of ventricular arrhythmias may explain by increased indexes of ventricular repolarization and their relationship with inflammation in RA patients.